2021
DOI: 10.1063/5.0039410
|View full text |Cite
|
Sign up to set email alerts
|

The optical and electrical properties of amorphous gallium/titanium co-doped indium oxide films based on oxygen flow dependence

Abstract: Amorphous gallium/titanium (Ga,Ti) co-doped indium oxide (In2O3) (GTiIO) films present significant potential as transparent conducting electrodes for use in flexible electronic devices. Amorphous GTiIO films were grown on silicon and glass substrates using linear-facing target sputtering and various oxygen flow rates. Transmittance was as high as 80% in the visible range for O2 flow rates of 0.3, 0.7, and 1.0 SCCM. The lowest resistivity was obtained at f(O2) = 0.3 SCCM with 0.47 mΩ cm. Dielectric functions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The peak at 530.7 eV is attributed to dissociative O − ions or oxygen vacancies. 30 This result means that there could be more defects on the surface of the material caused by the vacancy of the oxygen from the lattice. This change leads to an increased photocatalytic efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 530.7 eV is attributed to dissociative O − ions or oxygen vacancies. 30 This result means that there could be more defects on the surface of the material caused by the vacancy of the oxygen from the lattice. This change leads to an increased photocatalytic efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the thickness (d) of TCO films is also close to the transmittance and sheet resistance. Recent research has demonstrated the potential for replacing tin dopants in indium oxide with other metals, such as titanium [4], tungsten [5], molybdenum [6], and hafnium [7], to achieve higher carrier mobility and improved NIR transparency while maintaining comparable conductivity. However, the growth temperatures required for these TCOs tend to be relatively high (> 300 ℃), which exceeds the melting point of photoresists commonly used in many applications.…”
Section: Introductionmentioning
confidence: 99%